Chapter 13 Private audiovisual media archives in Greenland A case study of TV-Aasiaat's audiovisual archives from the 1990s - Fleischer, Aviaq (Taylor & Francis, 2024)
The national public service television station in Greenland (Kalaallit Nunaata Radioa & TV, abbreviated KNR) is undergoing a digitization of their non-digital media archives, to be completed in 2024. Yet, when KNR first began broadcasting television in 1982, after several years of planning, Greenland already had 25 private, local TV associations around the country. These private TV associations played an important part supplying local content to KNR. Today the number of private TV associations has decreased with only a couple of stations left, and their archives are not considered part of KNR's archive; instead, they are identified as private archives. Today they are dispersed both geographically and institutionally, often held in local museums if they have been kept at all, since these arrangements were up to the TV associations themselves. Even when they have been kept, the old tapes are at immediate risk of degrading irreparably unless they are digitized very soon. This chapter examines the media archives from TV-Aasiaat from the 1990s, surveying the content and condition of the non-digital tapes. Productions made by TV-Aasiaat and other local TV stations constitute an important part of the cultural heritage of modern Greenland, allowing a view of local everyday life told in Kalaallisut, whereas KNR's national broadcasts in the 1980s and 1990s were just as often in Danish as in Kalaallisut. The productions of the local TV stations ought to be recognized as Greenlandic cultural heritage and digitized for preservation along with KNR's own productions.